Monitoring of Ganoderma spp. on the trees at Arboretum of Universitas Gadjah Mada, Yogyakarta, Indonesia: Implications for health care recommendation of old trees. Issue 1 (November 2021) - Rahayu, S; Utomo, D S; Cahyanto, V E; Anggara, G; Adriyanti, D T; Nurjanto, H H; Kristian, A A
Abstract: The arboretum of Universitas Gadjah Mada (UGM), Yogyakarta, established in 1963, is host to various plants and trees originating from across Indonesia. Due to poor management and climate change, several cases of tree death and decline related to the Ganoderma sp. attack have been reported since 2015. The aims of this research were to evaluate the occurrence of root rot disease and to monitor the spatial and temporal distribution of Ganoderma spp. Completely survey on 638 trees with DBH more than 10 cm, monitored the number of basidiocarps attached on each infected species tree, and assessed the leaf and canopy condition were conducted on 2018 to 2021. The result showed that 0.78 % of trees with more than 10 cm diameter were infected by Ganoderma sp. since 2018 and become 1.57% in 2021. The species trees of Pterygota alata (1 tree), Pterocarpus indicus (1 tree), and Adenanthera pavonina (8 trees) were attacked by Ganoderma with a disease severity index of 25% to 100% in September 2021. The spatial pattern of trees associated with Ganoderma was random. However, since the density of trees at the arboretum is dense, the potential Ganoderma spreading through root contact will be high. Regular monitoring for early detection has to be conducted to prevent advanced infection and to set health care recommendations for infected trees with a high scientific value.